2016
DOI: 10.1259/bjr.20160624
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and dosimetric changes in patients with head and neck cancer treated with an integrated MRI-tri-60Co teletherapy device

Abstract: Objective: Prior studies have relied on CT to assess alterations in anatomy among patients undergoing radiation for head and neck cancer. We sought to determine the feasibility of using MRI-based image-guided radiotherapy to quantify these changes and to ascertain their potential dosimetric implications. Methods: 6 patients with head and neck cancer were treated with intensity-modulated radiotherapy (IMRT) on a novel tri- 60Co teletherapy system equipped with a 0.35-T MRI (VR, ViewRay Incorporated, Oakwood Vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Consequently, interval OAR/GTV deformations during therapy are unincorporated, and dose is "forward projected" with increasingly large temporal and geometric differential(s) from the planning scan. This approach is currently the default implementation for the 0.35T ViewRay system for MRguided RT systems (as detailed by Raghavan et al (30), in a study where registration of the MRI Fraction to the initial MRI planning was performed prior to manual segmentation), and the initial 510k-compliant 1.5T Elekta MR-LinAc configuration (2ATL), which allows rigid registration of MRI planning to daily fractions, and either a "adapt-to-point" (virtual isocentric alignment) or "adapt-to-shape" (volume-based replanning).…”
Section: Art Techniquesmentioning
confidence: 99%
“…Consequently, interval OAR/GTV deformations during therapy are unincorporated, and dose is "forward projected" with increasingly large temporal and geometric differential(s) from the planning scan. This approach is currently the default implementation for the 0.35T ViewRay system for MRguided RT systems (as detailed by Raghavan et al (30), in a study where registration of the MRI Fraction to the initial MRI planning was performed prior to manual segmentation), and the initial 510k-compliant 1.5T Elekta MR-LinAc configuration (2ATL), which allows rigid registration of MRI planning to daily fractions, and either a "adapt-to-point" (virtual isocentric alignment) or "adapt-to-shape" (volume-based replanning).…”
Section: Art Techniquesmentioning
confidence: 99%
“…Patients with OCC tend to experience changes in the soft tissue and flap throughout the course of RT, along with interfractional anatomic changes that may result in an unpredictable geographic miss. 5 - 8 , 30 Miyazaki et al reported that SIB with a sequential re-SIB plan had a significantly lower spinal cord Dmax than that of the initial SIB plan. 27 Additionally, the degree of dose inhomogeneity inside PTV1 was analyzed using the standard deviation parameter, demonstrating better homogeneity for the sequential technique and worse homogeneity for the SIB technique.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In contrast, if different dose levels are delivered simultaneously during IMRT to different target volumes within a single treatment fraction, that procedure is known as the "SIB-IMRT" technique. 2,4 Patients with head and neck squamous cell carcinoma (HNSCC) tend to undergo changes in soft tissues and body weight throughout the course of radiotherapy (RT), 5,6 causing great deviation in the dose delivered to the planning target volume (PTV) and normal tissues outside the PTV, 7 which may result in an unpredictable geographic miss. 8 Additionally, SIB-IMRT might present a risk of locoregional failure due to the low marginal doses when the doses given to the adjacent critical structures or other normal tissues are the major concern in the high-dose region.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of prospective clinical trials evaluating the objective benefit of ART for HNC, several dosimetric studies have been published so far, e.g., demonstrating an underestimation of the cumulative dose to the parotids when using the original non-adapted plan only, leading to increased probability for xerostomia ( 15 , 18 ). Raghavan et al were one of the first groups to demonstrate both a migration of the center of mass of the parotids, as well as a bilateral volume shrinkage in 6 HNC-patients, using an MRgRT-dedicated platform ( 19 ). An example of parotid migration and volume reduction demonstrated with the help of longitudinal imaging on the MR-Linac is shown on Figure 1A .…”
Section: Adaptive Treatment For Head and Neck Cancer And Potential Bementioning
confidence: 99%